Haiti : Can Preconditions for RBF be Established in Fragile States? - Adelman, Melissa; Baron, Juan; Lehe, Jonathan (World Bank, Washington, DC, 2018)
The Results in Education for All Children (REACH) Trust Fund at the World Bank provided funding to the Government of Haiti with the goal of establishing the preconditions for the adoption of RBF in the Haitian National Ministry of Education and Professional Training (Ministère de l'Education National et de la Formation Professionnelle, MENFP). To this end, the grant funded the development of a quality assurance system (QAS) based on specific standards for the most important dimensions of educational quality in the country. The idea was to include clear indicators for each quality dimension that would make it possible to measure education results on the ground. The grant also funded a series of complementary activities aimed at strengthening the technical capacity of MENFP staff to define and measure quality. By developing a QAS for all primary schools in the country, the grant aimed to improve governance, enhance the data systems needed to measure results, and establish the preconditions necessary to introduce an RBF mechanism in the education sector in Haiti.